A holistic approach to lead pipe scale analysis: Importance, methodology, and limitations. Issue 2 (17th March 2022) - Harmon, Stephen M.; Tully, Jennifer; DeSantis, Michael K.; Schock, Michael R.; Triantafyllidou, Simoni; Lytle, Darren A.
Abstract: With lead service lines (LSLs) remaining for decades to come, scale analyses are critical to helping limit lead exposure from drinking water. This laboratory has used an integrated suite of analytical techniques to characterize the elemental composition, mineral identification, and physical features of scales, helping the water industry to evaluate, predict, and reduce lead corrosion. The methods used in this laboratory to prepare and analyze the LSL scale, and guidance to achieving reliable and meaningful results, are described. Primary methods include the following: optical microscopy, powder X‐ray diffraction, inductively coupled plasma spectroscopy, X‐ray fluorescence, scanning electron microscopy with energy dispersive spectroscopy, combustion and coulometric analyses of C and S, and X‐ray absorption spectroscopy. Examples of associated pitfalls and ways to avoid them are provided, including pipe excavation/transport, sample preparation, analysis, and data interpretation. Illustrative examples are presented of practical scale analysis questions that could be answered by combinations of pipe scale analyses.